GAYA KEPEMIMPINAN INFORMAL PADA UPT PEMASYARAKATAN - Rifky Ananda Tarigan; Mitro Subroto (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
In society and in organizational environments, both formal and informal, there is always someone who is considered more than others, such a person is generally referred to as a leader. The existence of a leader is absolutely necessary in needing a leader figure. A leader needs to appear on behalf of his group as a place to take risks when there is pressure on a group and as a place to put power. The leader will also coordinate the group in carrying out every activity that will be made or a product. In the figure, a leader must also apply the principles and style of good leadership, because a leader not only brings personality but a group that certainly has different characters from one another. So in an association between individuals who form a group and stay in one place or move, it must have a leader figure who is able to bring them to a mutually agreed goal. For this reason, in order for a leader to be able to bring the group he leads, he must be trained and know the values of leadership and apply them to the group.